Induction of murine T-helper-cell responses to the filarial nematode Brugia malayi. - Pearlman, E (1993)
The purpose of this study was to examine the murine T-helper-cell (Th) cytokine response to the human filarial parasite Brugia malayi. In the first 14 days following intraperitoneal inoculation of live microfilariae into BALB/c mice, filarial antigen-driven splenic lymphoid cells produced gamma interferon (IFN-gamma) and little or no interleukin-5 (IL-5). After this time, IL-5 production increased (to 10 to 12 ng per 5 x 10(6) cells) coincident with a marked diminution in IFN-gamma generation. A single subcutaneous immunization with soluble microfilarial antigens also induced an IFN-gamma but no IL-5 response, whereas immunization three times elicited a predominant Th2-like reaction characterized by IL-4 and IL-5 production by CD4+ lymph node lymphocytes and a 10-fold increase in serum immunoglobulin E. The importance of IL-10 in establishing the balance between parasite-specific Th1 and Th2 responses was demonstrated by the ability of neutralizing monoclonal antibody to this cytokine to increase IFN-gamma production by splenic and lymph node cells from mice chronically exposed to live microfilariae or immunized multiple times with soluble filarial antigens.